(untitled) - Jekel, James F. (Philadelphia, 2001)
This is the only textbook for medical students and public health school students that combines the disciplines of epidemiology, biostatistics, preventive medicine, and public health in one convenient book. Written by renowned experts in the field, this text presents the information you need with a clinical slant using real-life medical examples throughout. Combining all four disciplines in one book creates an integrated approach that shows the interrelationships among these fields and stresses their clinical relevance. In addition to medical and public health school students, this text serves as a source of information for health care professionals who wish to study these topics on their own or to review for medical board examinations. A comprehensive examination including 350 USMLE-style questions with detailed answers and explanations is provided. This text is recommended by the American Public Health Association as one of the best sources for review for residents preparing for the boards in public health medicine.
Keywords: Epidemiology,Medical statistics,Medicine, preventive